Phaeohyphomycosis - Arcobello, Jonathan T.; Revankar, Sanjay G. (Seminars in Respiratory and Critical Care Medicine, 2020)
Phaeohyphomycosis refers to infections due to a large group of heterogenous organisms called “dematiaceous” or “melanized” fungi. These fungi are distinguished by the predominance of melanin in their cell walls, which likely acts as a virulence factor. Virtually, everyone is exposed to dematiaceous fungi through inhalation, as they are ubiquitous in the environment, although the development of infection is extremely uncommon. Invasive disease is rare but remains important due to the ability to cause serious disease in immunocompetent and immunocompromised hosts, unlike other fungal infections such as aspergillosis. A large variety of invasive manifestations can be caused by these organisms, including deep local infections, pulmonary infection, cerebral infection, and disseminated disease, which is associated with high mortality. While advances in molecular techniques are promising, they have still not replaced histology and culture as the primary diagnostic tools. Therapy is not standardized and is based primarily on clinical experience from descriptive case reports.
Keywords: dematiaceous; phaeohyphomycosis; melanized; voriconazole; posaconazole; itraconazole; amphotericin B